2007
DOI: 10.1111/j.1460-9592.2007.02330.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the adjustment of the Ambu laryngeal mask under magnetic resonance imaging

Abstract: The Ambu AuraOnce can be regarded as a safe product for airway maintenance in pediatric patients. No relationship was found between radiological measurements and sealing pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
3
10
2
Order By: Relevance
“…This finding contrasts that of Monclus et al17 who found no statistical difference between SGAD sizes. A significantly higher OPLP was noted in groups 2 and 3 between the 2 SGADs in favor of the i-gel.…”
Section: Discussioncontrasting
confidence: 98%
“…This finding contrasts that of Monclus et al17 who found no statistical difference between SGAD sizes. A significantly higher OPLP was noted in groups 2 and 3 between the 2 SGADs in favor of the i-gel.…”
Section: Discussioncontrasting
confidence: 98%
“…Regardless of inclusion of the data of infants weighing less than 10 kg, the subgroup analysis showed a statistically significant difference in the Ambu airway seal pressure: the smaller the child, the lower was airway seal pressure. This is in contrast to the findings of Monclus et al, 11 who found no statistical difference between the sizes. For the i-gel, more minor interventions and longer insertion times were necessary in the small sizes, which might indicate differences in mask performance according to children's age and weight.…”
Section: Discussioncontrasting
confidence: 57%
“…Previously published studies have demonstrated the easy insertion and placement of the Ambu and attributed this characteristic to the shape of the device, with its 90-degree tube angle, which seems to fit laryngeal anatomy very well. 11,14,24 Comparing the angle of both devices used in our study, the Ambu indeed shows a more pronounced airway angle ( fig. 2), which might fit anatomically better into the hypopharynx and onto the laryngeal inlet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations